Experimental study on a variable magnet length cusped field thruster. (May 2015) - Ma, Chengyu; Liu, Hui; Hu, Yanlin; Yu, Daren; Chen, Pengbo; Sun, Guoshun; Zhao, Yinjian
Abstract: The cusped field thruster is an emerging kind of electric propulsion equipment employing a cusped magnetic field to achieve potentially long lifetime. As important factors contributing to the thruster performance, the optimal channel length and magnetic field design are still uncertain. In order to research how magnet length affects performance, a variable magnet length cusped field thruster (VML-CFT) was designed and tested in Harbin Institute of Technology (HIT). By using modular magnets, VML-CFT can vary the length of each cusp stage. The design of VML-CFT is demonstrated in this paper. Experimental results show that certain length increase of the middle stage can improve the thruster performance. By analyzing experimental results with different magnet lengths, the thruster internal physical process can be inferred. Highlights: The concept of a variable magnet length cusped field thruster is proposed. The detailed design of the thruster is introduced. By prolonging the middle stage, the thruster performance can be improved. Longer middle stage can increase magnetic mirror effect and enlarge ionization volume.